Blockchain in supply chain management: a grounded theory-based analysis - Rodrigues, Eladian Batista [UNESP] (2021)
Purpose: This study aims to present consolidated information on blockchain, which seeks to better clarify the concept of blockchain and the associated implications and characteristics. Design/methodology/approach: The methodological procedure used was Grounded Theory, based on a Systematic Bibliographic Review on the adoption of blockchain in supply chain management. To add experts' opinion on the subject to the analyzed panorama, data from a survey were also considered in the analysis. Findings: The Grounded Theory enabled the development of consolidated information on blockchain related knowledge, identifying benefits, fragilities and contributions of the concept for supply chain management. Originality/value: An epistemological gap has been identified between the use of blockchain in supply chain management and a theoretical basis to support the application. The originality of this study lies in providing a proposition of this theoretical basis.